Functional Specialization of Duplicated AGAMOUS Homologs in Regulating Floral Organ Development of Medicago truncatula - Zhu, Butuo; Li, Hui; Wen, Jiangqi; Mysore, Kirankumar S.; Wang, Xianbing; Pei, Yanxi; Niu, Lifang; Lin, Hao (Frontiers in Plant Science, 2018)
The C function gene AGAMOUS (AG) encodes for a MADS-box transcription factor required for floral organ identity and floral meristem determinacy in angiosperms. Unlike Arabidopsis, most legume plants including Medicago truncatula possess two AG homologues arose by an ancient genome duplication event. Despite two AGAMOUS homologues MtAGa and MtAGb have been recently characterized and shown to fulfill the C function activity, the functional specialization of duplicated MtAG homologs and how they interact with other floral organ identity genes during M. truncatula floral morphogenesis remains to be elucidated. Here we investigated the functions of duplicated AG homologues MtAGa and MtAGb by characterizing their loss-of function mutants in depth. Lack of MtAGa function in M. truncatula leads to serious defects in carpel fusion and ovule formation, resulting in split carpels and producing abnormal pods with reduced seed number, while loss-of-function of MtAGb leads to an incomplete fusion of staminal tubes with weak stamen-petaloid conversion. Genetic analysis confirmed that MtAGa and MtAGb together fulfill a full C-function activity, but the stamens and carpels are completely converted to numerous vexillum-like petals in the double mutant of mtaga mtagb, which is distinguished from Arabidopsis ag. Further qRT-PCR analysis in different mtag mutants revealed that MtAGa and MtAGb can repress the expression of putative A and B function genes as well as MtWUS, but promote putative D function genes expression in M. truncatula. In addition, we found that the abnormal dorsal petal phenotype observed in the mtaga mtagb double mutant is associated with the upregulation of CYCLOIDEA (CYC)-like TCP genes. Taken together, our data suggest that the redundant MtAGa and MtAGb genes of M. truncatula employ a conserved mechanism of action similar to Arabidopsis in determining floral organ identity and floral meristem determinacy but may have evolved distinct function in regulating floral symmetry by coordinating with specific floral dorsoventral identity factors.